Application of biological agents in the treatment of anti-neutrophil cytoplasmic antibody-associated vasculitis - Liu, Weijun; Tian, Guanyuan; Chen, Chao; Zhang, Mingying; Chen, Zhanmao; Chen, Tietao; Lin, Zhibin; Wu, Wuzhong; Wu, Yiqaing; Wu, Kefei; Liu, Qinghua (Frontiers in Pharmacology, 2024)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) has been traditionally treated using glucocorticoids and immunosuppressants. However, these treatment modes are associated with high recurrence AAV rates and adverse reactions. Therefore, treatment strategies for AAV need to be urgently optimized. The efficacy and safety of biological agents in the treatment of vasculitis have been clinically validated. This review comprehensively summarizes the evidence -based support for the clinical use of existing biological agents in AAV. The findings reveal that multiple biological agents not on ly effectively reduce the adverse reactions associated with glucocorticoids and immunosuppressants but also demonstrate significant therapeutic efficacy. Notably, rituximab, an anti -CD20 antibody, has emerged as a first -line treatment option for AAV. Mepolizumab has shown promising results in relapsed and refractory eosinophilic granulomatosis with polyangiitis.Other biological agents targeting cytokines, complement, and other pathways have also demonstrated clinical benefits in recent studies. The widespread application of biological agents provides new insights into the treatment of AAV and is expected to drive further clinical research. These advancements not only improve patient outcomes but also offer more possibilities and hope in the field of AAV treatment.